Biodiversity status of the Mekong Delta, Vietnam - Nguyễn, D.T.; Pham, T.T.; Tăng Thi, K.H. (CIFOR-ICRAF, 2024)
This report aims to provide an up-to-date status report of biodiversity in the Mekong Delta in Vietnam. It also discusses opportunities and challenges for enhancing biodiversity in the region. This report is developed based on an extensive literature review and in-depth interviews with eight experts and six policymakers who have engaged in developing biodiversity policies and programmes in Vietnam for the last two decades.